Facile synthesis and characterization of beta lactoglobulin–copper nanocomposites having antibacterial applications. Issue 88 (9th September 2016) - sardar, Subrata; Maity, Sanhita; Pal, Sampa; Parvej, Hasan; Das, Niloy; Sepay, Nayim; Sarkar, Manas; Halder, Umesh Chandra
Abstract : The synthesis of Cu 0 nanoparticles and Cu–protein nanocomposites is a great challenge. Abstract : The synthesis of Cu 0 nanoparticles and Cu–protein nanocomposites is a great challenge. Here we describe a simple and convenient method for the synthesis of Cu–β-lactoglobulin nanocomposites using very cheap CuSO4 ·5H2 O and the retinol binding model protein bovine β-lactoglobulin (β-lg) at pH 10.0 in ammoniacal medium. Then addition of hydrazine hydrates in the reaction mixture and heating the solution at 55 °C for 2 h resulted in the formation of hexagonal Cu–β-lg nanocomposite (average size 0.5 μm) containing the embedded Cu-nanoparticles as revealed from SEM and TEM analysis. The important feature of this method is that the highly stable Cu-nanoparticle present in the composites were synthesized without employing any inert atmosphere; decomposition of hydrazine hydrate generated the nitrogen in situ which produced the inert atmosphere for this reaction. Synthesis of this nanocomposite is justified by a docking study. The synthesized nanocomposite exhibits potential antibacterial activity against both Gram positive and Gram negative bacterial strains. Thus it can be employed in different medical applications and also in the preparation of various nanomedicines.